Cardiac Structure and Function in Morbidly Obese Parturients: An Echocardiographic Study. (August 2019) - Buddeberg, Bigna S.; Fernandes, Nicole L.; Vorster, Adri; Cupido, Blanche J.; Lombard, Carl J.; Swanevelder, Justiaan L.; Girard, Thierry; Dyer, Robert A.
Abstract : BACKGROUND: The increasing prevalence of obesity worldwide is a major threat to global health. Cardiac structural and functional changes are well documented for obesity as well as for pregnancy, but there is limited literature on morbidly obese parturients. We hypothesized that there are both cardiac structural and functional differences between morbidly obese pregnant women and pregnant women of normal body mass index (BMI). METHODS: This prospective cross-sectional study was performed in 2 referral maternity units in Cape Town, South Africa, over a 3-month period. Forty morbidly obese pregnant women of BMI ≥40 kg·m −2 (group O) were compared to 45 pregnant women of BMI ⩽30 kg·m −2 (group N). Cardiac structure and function were assessed by transthoracic echocardiography, according to the recommendations of the British Society of Echocardiography. The 2-sample t -test with unequal variances was used for the comparison of the mean values between the groups. RESULTS: Acceptable echocardiographic images were obtained in all obese women. Statistical significance was defined as P < .0225 after applying the Benjamini–Hochberg correction for multiple testing. Mean (standard deviation) mean arterial pressure was higher in group O (91 [8.42] vs 84 [9.49] mm Hg, P < .001). There were no between-group differences in heart rate, stroke volume, or cardiac index (84 [12] vs 79 [13] beats·minute −1, P = .103; 64.4 [9.7] vs 59.5 [13.5] mL, P = .069; 2551 [474] vs 2729 [623] mL·minute −1 ·m −2, P = .156, for groups O and N, respectively). Stroke volume index was lower, and left ventricular mass was higher in group O (30.14 [4.51] vs 34.25 [7.00] mL·m −2, P = .003; 152 [24] vs 115 [29] g, P < .001). S′ septal was lower in group O (8.43 [1.20] vs 9.25 [1.64] cm·second −1, P = .012). Considering diastolic function, isovolumetric relaxation time was significantly prolonged in group O (73 [15] vs 61 [15] milliseconds, P < .001). The septal tissue Doppler index E′ septal was lower in group O (9.08 [1.69] vs 11.28 [3.18], P < .001). There were no between-group differences in E′ average (10.7 [2.3] vs 12.0 [2.7], P = .018, O versus N) or E/E′ average (7.85 [1.77] vs 7.27 [1.68], P = .137, O versus N). Right ventricular E′/A′ was lower in group O (1.07 [0.47] vs 1.29 [0.32], P = .016). CONCLUSIONS: Cardiac index did not differ between obese pregnant women and those with normal BMI. Their increased left ventricular mass and lower stroke volume index could indicate a limited adaptive reserve. Obese women had minor decreases in septal left ventricular tissue Doppler velocity, but the E/E′ average values did not suggest clinically significant diastolic dysfunction.